2016
DOI: 10.5296/jse.v6i2.9402
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Acculturation Attitude and Translation of Culture-Bound Texts

Abstract: <p>Acculturation attitudes, referred to as “sojourner reactions to adaptation into new language and cultural communities” (Culhane, 2004: 51), can be a predictor of translators’ level of intercultural competence during educational sojourns. Intercultural competence, defined as a “complex of abilities needed to perform effectively and appropriately when interacting with others who are linguistically and culturally different from oneself” (Fantini 2006: 12), can accordingly be a predictor of translation qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…The findings obtained in the current study are in line with the findings obtained in the studies conducted by Shehab (2004), Bruti (2006), Hassani-Laharomi (2013), and Rafieyan (2016) who found that knowledge of the source language pragmalinguistic and sociopragmatic perspectives contributes to a great extent to the quality of translation of the source language pragmatic perspectives into the target language. The findings obtained in the current study also support the findings obtained in the studies conducted by Rafieyan et al (2014a) and Rafieyan et al (2014c) who found that pragmatic instruction has a significant effect on the Journal for the Study of English Linguistics ISSN 2329-7034 2016…”
supporting
confidence: 92%
See 1 more Smart Citation
“…The findings obtained in the current study are in line with the findings obtained in the studies conducted by Shehab (2004), Bruti (2006), Hassani-Laharomi (2013), and Rafieyan (2016) who found that knowledge of the source language pragmalinguistic and sociopragmatic perspectives contributes to a great extent to the quality of translation of the source language pragmatic perspectives into the target language. The findings obtained in the current study also support the findings obtained in the studies conducted by Rafieyan et al (2014a) and Rafieyan et al (2014c) who found that pragmatic instruction has a significant effect on the Journal for the Study of English Linguistics ISSN 2329-7034 2016…”
supporting
confidence: 92%
“…However, in the post-revolution era, translators' tendency to preserve the implicatures decreased. Most recently, Rafieyan (2016) investigated the relationship between translation students' level of pragmatic comprehension ability and the quality of their translations of source language implicatures. Participants of the study were a group of Iranian undergraduate students of English at a university in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that developing language proficiency and mere immersion in a target language does not develop pragmatic competence. Therefore, in order to develop pragmatic competence in language learners, classroom instruction should be equipped with pragmalinguistic and sociopragmatic features of the target language (Rafieyan, 2016a;Rafieyan, 2016b;Rafieyan, 2016d;Rafieyan, 2016e).…”
Section: Resultsmentioning
confidence: 99%
“…The study found that there is a strong positive relationship between the degree of acculturation attitude toward target language culture and the pragmatic comprehension ability. Most recently, Rafieyan (2016) explored the relationship between language learners' acculturation attitudes and the quality of their translation of culture-bound texts. Participants of the study were a group of Iranian postgraduate students of English translation at universities in England.…”
Section: Introductionmentioning
confidence: 99%